Protein import into mitochondria - Lithgow, Trevor (Henry Stewart Talks, 2007)
Introduction to protein import pathways, Structure and function of targeting sequences, Protein import into the matrix, intermembrane space and membranes of mitochondria, Biochemical assays and bioinformatics for studying protein import, The TIM complex in parasites of humans, The TOM complex in animals and plants, The evolution of protein import into mitochondria
Reviewed at 2022/04/12